Replication in the long nineteenth century : re-makings and reproductions - Codell, Julie F.; Hughes, Linda K. (Edinburgh University Press Ltd, 2018)
"The first study of nineteenth-century replication across art, literature, science, social science and humanities. This landmark study explores replication as a nineteenth-century phenomenon. Replication, defined by Victorian artists as subsequent versions of a first version, similar but changed, occurred in art, literature, the press, merchandising, and historical reproductions in architecture and museums. Replication also shaped scientific concepts in biology and geology and scientific practices in laboratories that repeated experiments as part of the scientific method. Fourteen case studies map a range of nineteenth-century replication practices and associations across art, literature, science, media and material culture. While replication stirred imaginations as well as anxieties over the industrialisation that produced a modern mass culture, 'Replication in the Long Nineteenth Century' suggests, nonetheless, that this phenomenon is a forerunner of our contemporary digital culture"--Back cover